Maternal cobalt concentration and risk of spontaneous preterm birth: the role of fasting blood glucose and lipid profiles - Huang, Junhua; Zheng, Wei; Wang, Aili; Han, Weiling; Chen, Junxi; An, Hang; Yan, Lailai; Li, Zhiwen; Li, Guanghui (Frontiers in Nutrition, 2024)
Spontaneous preterm birth (SPB) is a significant cause of neonatal mortality, yet its etiology remains unclear. Cobalt, an essential trace element, might be a risk factor for SPB. This study aims to investigate the relationship between maternal serum cobalt concentration and SPB, and to clarify the role of blood lipids and fasting blood glucose (FBG) in this relationship. Serum samples were obtained from 222 pregnant women with SPB and 224 controls during the first (7-13 weeks of pregnancy) and third trimesters (32-42 weeks of pregnancy). Serum cobalt concentration was determined using inductively coupled plasma mass spectrometry (ICP-MS). Fasting blood glucose and lipids levels were detected using a fully automated biochemical immunoassay instrument. Logistic regression models and linear regression models were established to explore the association between serum cobalt concentration and the risk of SPB in pregnant women, and to test the mediating effect of fasting blood glucose (FBG) and lipids. We found that the serum cobalt concentration in mothers with SPB and controls was similar in the first trimester, with values of 0.79 (0.58-1.10) ng/mL and 0.75 (0.51-1.07) ng/mL, respectively. However, in the third trimester, the cobalt concentration increased to 0.88 (0.59-1.14) ng/mL and 0.84 (0.52-1.19) ng/mL, respectively. In the logistic regression model, when considering the third trimester of pregnancy, it was observed that the medium level of cobalt concentration (0.63-1.07 ng/ml) had a negative correlation with the risk of SPB. The odds ratio (OR) was 0.56, with a 95% confidence interval of 0.34-0.90 ng/mL and a p-value of 0.02. This suggests that cobalt in this concentration range played a protective role against SPB. Additionally, it was found that FBG in the third trimester of pregnancy had a partial intermediary role, accounting for 9.12% of the association. However, no relationship between cobalt and SPB risk was found in the first trimester. In the future, a multi-center study with a larger sample size is needed to clarify the appropriate range of cobalt concentrations during pregnancy for different populations, and to explore the specific mechanism of FBG mediating role, so as to provide new ideas for better prevention of SPB.